Physiological and Biochemical Responses, and Comparative Transcriptome Profiling of Two Angelica sinensis Cultivars Under Enhanced Ultraviolet-B Radiation - Peng, Tong; Wang, Yinquan; Yang, Tao; Wang, Fusheng; Luo, Jun; Zhang, Yali (Frontiers in Plant Science, 2021)
In this study, we explored the adaptive mechanism of two varieties of Angelica sinensis exposed to enhanced Ultraviolet-B(UV-B) radiation. The radiation had different effects on the biomass, photosynthetic performance, oxidative damage, antioxidant defense system, and levels of bioactive compounds of Mingui 1 (C1) and Mingui 2 (C2). C2 outperformed C1 under enhanced UV-B radiation, compared to natural light. Using the Illumina RNA-seq, we obtained 6,326 and 2,583 DEGs in C1 and C2, respectively. Under enhanced UV-B radiation, the mRNA levels of genes involved in photosynthesis, antennae protein synthesis, carbon fixation, chlorophyll synthesis, and carotenoid synthesis were decreased in C1 but stable in C2, involving few DEGs. TFs were widely involved in the response of C1 to enhanced UV-B radiation; almost all bHLH and MYB coding genes were downregulated whereas almost all genes encoded WRKY22, WRKY50, WRKY72, NCF, and HSF were upregulated. These results indicate that enhanced UV-B radiation was not conducive to the synthesis of flavonoids, while disease resistance was enhanced. Regarding the ROS scavenging system, upregulated DEGs were mainly found in the AsA-GSH cycle and PrxR/Trx pathways. Remarkably, DEGs that those encoding biosynthetic key enzymes, including ferulic acid (CHS, CHI, DFR, and ANS) and flavonoid (CHS, CHI, DFR, and ANS), most upregulation in C2, leading to increased accumulation of ferulic acid and flavonoids and adversely affecting C1. Genes encoding key enzymes involved in the synthesis of lactone components (ACX, PXG) were mostly up-regulated in C1, increasing the content of lactone components. Our results reveal the DEGs present between C1 and C2 under enhanced UV-B radiation and are consistent with the observed differences in physiological and biochemical indexes. C1 was more sensitive to enhanced UV-B radiation, and C2 was more tolerant to it under moderate enhanced UV-B radiation stress. In addition, the large amount of A. sinensis transcriptome data generated here will serve as a source for finding effective ways to mitigate UV-B enhancement, and also contribute to the well-established lack of genetic information for non-model plant species.